Bone mass in female volleyball players: a comparison of total and regional bone mass in female volleyball players and nonactive females - Alfredson, H.; Nordstrom, P.; Lorentzon, R. (Calcified Tissue International, 1997)
The purpose of this cross-sectional study was to evaluate bone mass in female athletes participating in an impact loading sport (volleyball), and especially to investigate whether any changes in bone mass might be related to the type and magnitude of weightbearing loading and muscle strength. The volleyball group consisted of 13 first division players (age 20.9 +/- 3.7 years) training for about 8 hours/week, and the reference group consisted of 13 nonactive females (age 25.0 +/- 2.4 years) not participating in any kind of regular or organized sport activity. The groups were matched according to weight and height. Areal bone mineral density (BMD) was measured in total body, head, lumbar spine, femoral neck, Ward's triangle, trochanter, the whole femur, and humerus using dual-energy-X-ray absorptiometry. Isokinetic concentric peak torque of the quadricep and hamstring muscles was measured using an isokinetic dynamometer. Compared with the controls, the volleyball players had a significantly (P < 0.05-0.01) higher BMD of the total body (6.1%), lumbar spine (13.2%), femoral neck (15.8%), Ward's triangle (17.9%), trochanter (18.8%), nondominant femur (8.2%), and humerus (dominant 9.5%, nondominant 10.0%), but not of the head and the dominant whole femur. The dominant humerus showed significantly higher BMD than the nondominant humerus in both the volleyball and nonactive group (P < 0.05). There was no significant difference in muscle strength of the thigh between the two groups. In the nonactive group, muscle strength in the quadriceps, and especially hamstrings, was correlated to BMD of the adjacent bones (whole femur, hip sites) and also to distant sites (humerus). However, in the volleyball group there were no correlations between muscle strength and BMD of the adjacent bones, but quadricep strength correlated to BMD of the humerus. These results clearly show that young female volleyball players have a high bone mass. The demonstrated high bone mass seems to be related to the type of loading subjected to each BMD site. Muscle strength of the thigh seems to have little impact on BMD in female volleyball players.